Language development in infants: What do humans hear in the first months of life?. (September 2013) - Langus, Alan; Nespor, Marina
Abstract: In this article we discuss experimental work on language acquisition that we have carried out in recent years. We first describe the most common methods used in infant research, then we concentrate on linguistic rhythm and the aspects of language that might be learned in the first year of life on the basis of signals contained in the speech stream. These include the basic level of rhythm carried by the two most basic phonological categories of consonants and vowels, and rhythmic alternation at the phrase level and its signal to syntax. Because linguistic rhythm is one of the first aspects of language that infants perceive and represent, the research discussed may help to diagnose hearing problems and lead to new ways of training individuals with speech impairments.